Subjective and material factors influencing the presence of mosquito breeding sites in large-scale household waste in Asunción, Paraguay - Lima-Pereira, Patricia (2024)
Within households, bulky solid waste serves as the predominant breeding ground for mosquitoes that transmit dengue fever. The aim of this study is to identify and describe the relationship between material and subjective factors, using socioecological theoretical frameworks for health prevention. A descriptive cross-sectional study is conducted, using a simple random sample of 350 households in Asunción, Paraguay. To compare households based on the presence or absence of large breeding sites, the chi-square test, non-parametric Mann–Whitney–Wilcoxon statistical test, and Yuen's robust T statistical test is employed. Additionally, a multivariate logistic regression analysis was carried out to determinate the Odd Ratio (OR). The study concludes that individualistic approaches in dengue prevention must be transcended and management capacities in homes must be increased by addressing environmental barriers and social beliefs, given the factor that most significantly explaines the presence of obsolete objects in homes is the belief that these items could prove useful in the future. In the multivariate analysis, the perception of usefulness of the potential breeding sites was one of the two significant variables that explain this behavior. The other significant variable was the low coverage of waste collection.